2007
DOI: 10.1213/01.ane.0000287655.95619.fa
|View full text |Cite
|
Sign up to set email alerts
|

The Paramedian Technique: A Superior Initial Approach to Continuous Spinal Anesthesia in the Elderly

Abstract: In summary, after the initial attempt, the paramedian approach is associated with an increased success rate, compared with the midline approach, during the performance of CSA in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 7 publications
2
73
1
Order By: Relevance
“…The most important determinants of subarachnoid distribution of local anesthesia are baricity, dosage, and site of injection [28], even though the mean dose of isobaric 0.5% bupivacaine in the hypotension group was not larger than in the nonhypotension group. The paramedian approach has been recommended for subarachnoid puncture in elderly patients and is associated with a high success rate [29]. In the paramedian approach, the needle is often directed in a cephalad direction and isobaric 0.5% bupivacaine may spread to a high sensory level [30]; more hypotension group patients underwent puncture via the paramedian approach than the nonhypotension group.…”
Section: Discussionmentioning
confidence: 99%
“…The most important determinants of subarachnoid distribution of local anesthesia are baricity, dosage, and site of injection [28], even though the mean dose of isobaric 0.5% bupivacaine in the hypotension group was not larger than in the nonhypotension group. The paramedian approach has been recommended for subarachnoid puncture in elderly patients and is associated with a high success rate [29]. In the paramedian approach, the needle is often directed in a cephalad direction and isobaric 0.5% bupivacaine may spread to a high sensory level [30]; more hypotension group patients underwent puncture via the paramedian approach than the nonhypotension group.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mericq O et al concluded that in patients who are elderly and with spinal deformity, PMA is a safe alternative with success rate of 100%. 6 Ahsan ul-haq et al demonstrated that success rate with paramedian approach was 100% with the first attempt success rate of 60%.…”
Section: 4mentioning
confidence: 99%
“…The paramedian and median techniques in which combined spinal epidural anesthesia was performed in 40 patients who underwent hip surgery were compared; while there was no difference in terms of complications, paramedian technique was found to be more successful (12). In another study, while the median approach was found to fail in elderly patients who had spinal deformities and for whom general anesthesia was more risky, the paramedian approach was 100% successful, and it was emphasized that the paramedian technique could be an alternative to general anesthesia in this patient profile (13).…”
Section: Discussionmentioning
confidence: 99%